Radiosynthesis of [thiocarbonyl-11C]disulfiram and its first PET study in mice. Issue 6 (15th March 2020) - Ishii, Hideki; Yamasaki, Tomoteru; Yui, Joji; Zhang, Yiding; Hanyu, Masayuki; Ogawa, Masanao; Nengaki, Nobuki; Tsuji, Atsushi B.; Terashima, Yuya; Matsushima, Kouji; Zhang, Ming-Rong
Graphical abstract: Abstract: [ Thiocarbonyl - 11 C]disulfiram ([ 11 C]DSF) was synthesized via iodine oxidation of [ 11 C]diethylcarbamodithioic acid ([ 11 C]DETC), which was prepared from [ 11 C]carbon disulfide and diethylamine. The decay-corrected isolated radiochemical yield (RCY) of [ 11 C]DSF was greatly affected by the addition of unlabeled carbon disulfide. In the presence of carbon disulfide, the RCY was increased up to 22% with low molar activity ( Am, 0.27 GBq/μmol). On the other hand, [ 11 C]DSF was obtained in 0.4% RCY with a high Am value (95 GBq/μmol) in the absence of carbon disulfide. The radiochemical purity of [ 11 C]DSF was always >98%. The first PET study on [ 11 C]DSF was performed in mice. A high uptake of radioactivity was observed in the liver, kidneys, and gallbladder. The uptake level and distribution pattern in mice were not significantly affected by the Am value of the [ 11 C]DSF sample used. In vivo metabolite analysis showed the rapid decomposition of [ 11 C]DSF in mouse plasma.